Analisis Penawaran Jagung di Jawa Tengah - Setyowati, Setyowati; Agustono, Agustono; Maharani, Marlisa (Caraka Tani: Journal of Sustainable Agriculture, 2004)
This research aims to analyze some factors that influence the corn supply in Central Java, and to analyze the corn supply elasticity in Central Java. The basic method used in this research is descriptive method. The location of this research stated with purposive, that is Central Java Province. And the data used in this research is secondary data.The analysis results the value of adjusted determination coefficient that is 87,6% and F-test analysis results that F-count (18,632) is greater than F-table (3,79) means that all the independent variables used in this research, which are corn’s harvested area in the recent year, corn’s production in the previous year, corn’s price in the previous year, peanut’s price in the previous year, urea fertilizer’s price in the previous year and the average of rainfall along the plant time influence in the together to the corn supply in Central Java. The results of t-test shows that corn’s harvested area in the recent year, corn’s production in the previous year, corn’s price in the previous year and urea fertilizers price in the previous year variables are the significant influential independent variables to the corn supply in Central Java. While based on the partial regression coefficient value of the significant influential independent variables, it is found that the corn’s harvested area in the recent area year has the highest value (0,992), so this variable has the greatest influence to the corn supply in Central Java.The corn supply elasticity in Central Java to the harvested area (0,948), corn’s production in the previous year (0,434), corn’ price in the previous year (0,709), urea fertilizer’s price in the previous year (0,161) in short-run is tend to be inelastic. While in long-run, corn’s supply is tend to be elastic to the corn’s harvested are (1,696) and corn’s price in the previous year (1,296). And corn supply is tend to be inelastic to the corn’s production in the previous year (0,777) and urea fertilizer’ price in the previous year (0,289).The results of this research shows that the corn’s farmers in Central Java in planting corn take the decisions based on profit (profit oriented) and have high response of the changing of corn’s harvested area in Central Java.